2007
DOI: 10.1159/000104166
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Regulation of the Trefoil Factor Family Binding Protein GKN2 (GDDR/TFIZ1/blottin) in Human Gastrointestinal Epithelial Cells

Abstract: Trefoil factor family (TFF) peptides are major secretory products of mucous epithelia and play a multifunctional role in cytoprotection, apoptosis, and immune response. Recently, a TFF2-binding protein was discovered in mice and named blottin. It is down-regulated in gastric cancer (GDDR), abundant in human gastric surface (TFIZ1) and its similarity to gastrokine-1 led to the gene’s name GKN2. To investigate the mode of GKN2 regulation activity of a luciferase reporter gene, controlled by the GKN2 promoter, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 62 publications
3
35
0
Order By: Relevance
“…At that time, a mouse homologue of GKN2 was characterized (formerly termed blottin) and non-covalent binding to a TFF2 fusion protein was reported [7,8]. GKN2 is one of the most up-regulated genes after Helicobacter pylori eradication [9] and it shows a similar regulation pattern with respect to cytokines as the TFF genes [10].…”
Section: Introductionmentioning
confidence: 99%
“…At that time, a mouse homologue of GKN2 was characterized (formerly termed blottin) and non-covalent binding to a TFF2 fusion protein was reported [7,8]. GKN2 is one of the most up-regulated genes after Helicobacter pylori eradication [9] and it shows a similar regulation pattern with respect to cytokines as the TFF genes [10].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the similar expression and biological functions, it was reasonable to speculate that there is some possible relationships between TFF1 and GKN1. GKN2 is a downstream gene of GKN1 and belongs to gastroinkase family (23). Recent studies have shown that GKN2 may interact with TFF1 to be a heterodimer.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, GKN1 and TFF1 were similar in both the expressed location and physical functions. GKN2, a number of gastrokine family, also contains a BRICHOS domain and is a downstream gene of GKN1 (23). Several studies found that GKN2 combined with TFF1 as a heterodimer to maintain the stabilization of mucosa (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…However, PPARγ agonists have been reported to foster ulcer healing [20] and protect against gastric ischemiareperfusion damage [19]. Possibly, the stimulating effect on gastric acid secretion is overridden by the simultaneous stimulating effect on trefoil factor expression [17], which are known to exert protective effects [18].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, they may induce apoptosis [16]. In gastric tissue, PPARγ agonists stimulate expression of trefoil factors , which in turn exert protective effects [18]. Accordingly, activation of PPARγ by its agonists may protect against gastric ischemia reperfusion damage [19] and foster ulcer healing [20].…”
Section: Introductionmentioning
confidence: 99%